2008
DOI: 10.1007/s10681-008-9840-0
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of new in vitro androgenesis-derived double haploids of barley

Abstract: Although barley is extensively grown in the Peruvian highlands as a food crop, agricultural and quality performance have historically been poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 18 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Similarly, ‘AC Andrew’ is an anther culture–derived DH line that accounted for 99% of the Canada Western Soft White Spring acreage. Recent assessments of the value of DH barley varieties have been provided by Gomez‐Pando et al. (2009a,b).…”
Section: Exploitationmentioning
confidence: 99%
“…Similarly, ‘AC Andrew’ is an anther culture–derived DH line that accounted for 99% of the Canada Western Soft White Spring acreage. Recent assessments of the value of DH barley varieties have been provided by Gomez‐Pando et al. (2009a,b).…”
Section: Exploitationmentioning
confidence: 99%
“…Doubled haploids have been widely employed in barley breeding programs, resulting in the release of several cultivars (see Muñoz-Amatriaín et al, 2008). Androgenesis-based DH-technique was used to produce barley varieties better suited to Peruvian highlands where barley is extensively grown as a food crop (Gomez-Pando et al, 2009).…”
Section: Traditional Plant Breedingmentioning
confidence: 99%
“…in this manner by doubling chromosomes in haploid plants it is possible to obtain genetically stable homozygous lines in a short time thereby providing a method for speeding up and increasing the selection efficiency. Such homozygous DH plants have been used in breeding programmes for production of pure lines and new highly adaptive and productive varieties (1,4,8,15,16,18,20,21,23,24,35,41,48). A number of studies (2,19,37,45,53,55) also reported that the obtained by the in vitro anther culture techniques haploids and Dh plants are an appropriate system for genetic manipulations, gene mapping and mutant line selection.…”
Section: Introductionmentioning
confidence: 99%